Aligning agendas for sustainable development in the post 2015 world. Issue 2 (11th November 2014) - Van Oers, Ron; Pereira Roders, Ana
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper is an editorial to JCHMSD's Volume 4 Issue 2 and its selection of papers. Design/methodology/approach – The paper presents some of the ongoing discussions at the international level on the establishment of new United Nations global objectives for development, known as the Sustainable Development Goals, which should guide progress in the world for the next 15 years. Two agendas for wise heritage management are discussed, one for the protection of nature and the other for better use of culture, which taken together could make a significant difference in stewarding the world's precious resources. Findings – While the previous Millennium Development Goals, established in 2000 as a set of eight goals with 19 targets, have been criticised as too broad, the current proposed Sustainable Development Goals, containing 17 goals and 169 targets to measure progress, are perhaps too many and too detailed and thereby risk failure of implementation. It also illustrates the ambition and the challenges of a pluralistic world with widely divergent priorities, reinforcing the idea of context-specificity of heritage conservation and resources management. Originality/value – This editorial further extends on the discussion that was started in the inaugural Editorial, of 2011, which stated that "the international debate is expected to intensify as regards a re-orientation of the concept of sustainability and to re-emphasise its meaning in clear and unambiguous terms" (JCHMSD, 1.1:9).